1981
DOI: 10.1002/dev.420140413
|View full text |Cite
|
Sign up to set email alerts
|

Volume discrimination learning in golden hamsters: Effects of the structure of complex rearing cages

Abstract: Golden hamsters (Mesocricetus auratus) were reared from birth to adulthood in a spatially diversified situation (EG); their performances were compared with those of other hamsters housed in standard laboratory cages (SG). The task was to discriminate between 2 cubic volumes of different sizes followed by various test situations designed to define the respective parts played by the 3 spatial dimensions during perception. The results show that surfaces of volumes were mainly taken into account by EG subjects whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has been known since Hebb (1949) initiated this research that animals from EC housing outperform the other 2 groups on complex, appetitively-motivated tasks such as mazes. Although this may in part reflect greater familiarity with large, open, spatially-complex environments, there is also evidence that EC animals use different strategies and have more well-developed concepts of the properties of objects (Juraska and others 1984;Thinus-Blanc 1981).…”
Section: Experience-dependent Brain Adaptationmentioning
confidence: 97%
“…It has been known since Hebb (1949) initiated this research that animals from EC housing outperform the other 2 groups on complex, appetitively-motivated tasks such as mazes. Although this may in part reflect greater familiarity with large, open, spatially-complex environments, there is also evidence that EC animals use different strategies and have more well-developed concepts of the properties of objects (Juraska and others 1984;Thinus-Blanc 1981).…”
Section: Experience-dependent Brain Adaptationmentioning
confidence: 97%
“…These results suggest that habituation processes occur more rapidly in heifers repeatedly regrouped than in heifers kept in stable pairs. Studies on rats and hamsters showed that animals reared in a restricted and small environment are less able to use environmental cues than animals reared in larger or more complex environments (Brown [10]; Thinus-Blanc [36,37]). These findings were confirmed by the results of Varty et al [39], who found that rats reared in an enriched environment acquire information from their environment more easily than rats reared in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Thinus-Blanc (1978) showed that such small mammals as the golden hamster were able to discriminate between two cubic volumes of different sizes and that in test situations they attended mainly to width, one of the three dimensions that defined the volume. Furthermore, Thinus-Blanc (1981) showed that this ability depended on rearing conditions, since subjects reared in spatially diversified cages were influenced by depth as well as width. In other words, the "enriched" animals were able to take into account the surfaces of volumes, whereas standard subjects used only one dimension-width.…”
Section: Discussionmentioning
confidence: 99%